ANALISIS SEMIOTIK IKLAN PARIWISATA NEGARA AUSTRALIA - Anak Agung Istri Manik Warmadewi (Universitas Warmadewa, 2019)
[Title: Semiotic analysis on Australian tourism advertisement] The aim of this study is to analyze the